African Perspectives on Religion and Climate Change - Chitando, Ezra; Conradie, Ernst M.; Kilonzo, Susan M. (My University, 2022)
Climate change, a global emergency, has become one of the most pressing issues of our time (see, for example, Religions for Peace 2016: 6; Satgar 2019; Gills and Morgan 2020; Cilliers 2021 (chapter 15); and IPCC 2021). Activists from diverse backgrounds have drawn attention to the urgency of addressing climate change, as it is an existential threat. The United Nations Sustainable Development Goal (SDG) Number 13 on climate action, itself closely con nected to other SDGs (Nerini et al. 2019), expresses the emerging consensus on the need to address climate change as a matter of urgency. It refers to the need to “take urgent action to combat climate change and its impacts.” As I shall argue throughout this chapter, Africa’s vulnerability to the impact of climate change calls for climate justice, which in turn is tied to human rights and sustainable development. Thus, “Climate justice links human rights and sustainable development to safeguard the rights of those affected by climate change”